Meaning Values in Diponegoro Poetry by Chairil Anwar: Critical Analysis - Guslina Wahyu Ningsih; Rosmawaty Harahap (JOURNAL OF SOCIETY INNOVATION AND DEVELOPMENT, 2024)
Diponegoro's poetry by Chairil Anwar is a literary work that has high aesthetic value. This poem also has high aesthetic value using beautiful words and harmonious rhythm. In this study, we conducted a critical analysis of the work to explore the aesthetic values contained therein. This research uses a qualitative descriptive method which is used to describe and illustrate existing phenomena, both natural and human engineering. The data collection technique used was an open questionnaire. The aim of writing an article about the story of Diponegoro's struggle in Chairil Anwar's poetry is to explore and reveal the meaning and values contained in the story. Apart from that, this article also aims to introduce Indonesian literary works to the wider community, especially the younger generation, so that they can better appreciate and understand the nation's cultural heritage. By discussing the story of Diponegoro's struggle through Chairil Anwar's poetry, it is hoped that we can feel the strength and fighting spirit that radiates from this national hero.